Unusual Formal [1+4] Annulation through Tandem P(NMe2)3‐Mediated Cyclopropanation/Base‐Catalyzed Cyclopropane Rearrangement: Facile Syntheses of Cyclopentenimines and Cyclopentenones. Issue 17 (15th March 2016) - Zhou, Rong; Zhang, Kai; Han, Ling; Chen, Yusong; Li, Ruifeng; He, Zhengjie
Abstract: An unusual formal [1+4] annulation of α‐dicarbonyl compounds with 1, 1‐dicyano‐1, 3‐dienes has been realized, leading to facile syntheses of cyclopentenimines and cyclopentenones in a unique manner. Mechanistic investigation implies that this reaction takes place through a P(NMe2 )3 ‐mediated cyclopropanation followed by a base‐catalyzed cyclopropane rearrangement. It therefore represents an unprecedented [1+4] annulation mode involving Kukhtin–Ramirez adducts. Abstract : Tandem ring generation : An unusual formal [1+4] annulation of α‐dicarbonyl compounds with 1, 1‐dicyano‐1, 3‐dienes via tandem P(NMe2 )3 ‐mediated cyclopropanation/base‐catalyzed cyclopropane rearrangement leads to facile syntheses of cyclopentenimines and cyclopentenones. Mechanistic investigation indicates the involvement of Kukhtin–Ramirez adducts.